The Determinants of Dividend Policy (an Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange 2016-2019 Period) - Nurni Arrina Lestari; Ade Sudarma; Antony Antony (Universitas Muhammadiyah Yogyakarta, 2021)
This research aims to analyze the factors that affect the company’s opportunities to distribute dividends, and based on those opportunities, this research further identifies the factors that affect the size of dividends to be distributed by the company. The research sample was taken from manufacturing companies listed on the Indonesia Stock Exchange for 2016-2019. The regression models used were logistic regression to analyze the variables affecting the company’s opportunities of dividends and multiple linear regression to analyze the variables affecting the size of the dividends to be distributed. This research finding revealed that the variables affecting the company’s opportunities of distributing dividends were profitability, liquidity, and company size. However, of the three variables, only profitability affected the size of the dividend distributed by the company.